Competition and Market Integration – Role of European Power Exchanges - Mrhač, Václav (2014)
The main focus of this thesis is to find out degree of market integration in power exchanges in the European Union. Well integrated electricity markets imply existence of single European electricity market and advanced level of liberalization process in this sector. The thesis provides estimates of degree of market integration for six most evolved European power exchanges. Therefore, British, Dutch, French, German, Spanish and Scandinavian power exchanges have been selected during sample period 2004 - 2012. After conducting correlation and convergence analysis, the results have not suggested existence of single European electricity market and prove the effect of liberalization at regional level.